Cross-cultural research - Delva, Jorge; Allen-Meares, Paula, 1948-; Momper, Sandra L. (New York ; Oxford : Oxford University Press, 2010)
This pocket guide offers researchers a framework for conducting research in a culturally sensitive manner with individuals families, and communities in diverse settings. This framework focuses on a process, rather than a typology of behaviours attitudes, values, and beliefs.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Research -- Methodology -- Cross-cultural studies; Social service -- Research -- United States -- Methodology -- Cross-cultural studies